2014
DOI: 10.1002/2014gl062190
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously measured lightning return stroke channel‐base current and luminosity

Abstract: The time delay between lightning return stroke current and the resultant luminosity was measured for 22 return strokes in eight lightning flashes triggered by the rocket-and-wire technique during the summer of 2014 in Florida. The current-to-luminosity delay measured at the channel base at the 20% amplitude level ranged from 30 to 200 ns with an average of 90 ns and at the 50% amplitude level ranged from 30 to 180 ns with an average of 94 ns. The delays are significantly shorter than that predicted by Liang et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 17 publications
6
30
0
Order By: Relevance
“…Their Figure suggests that the decay in upward propagating luminosity for four dart‐stepped‐leader light pulses is exponential. An exponential decay constant of 22 m reduces the current amplitude to about 10% of its peak in 50 m, although the relationship between current and luminosity is not well understood [e.g., Liang et al , ; Carvalho et al , ]. Furthermore, the use of an exponential current decay allows a direct comparison between results here and those previously reported by Jerauld [] and Howard et al [].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Their Figure suggests that the decay in upward propagating luminosity for four dart‐stepped‐leader light pulses is exponential. An exponential decay constant of 22 m reduces the current amplitude to about 10% of its peak in 50 m, although the relationship between current and luminosity is not well understood [e.g., Liang et al , ; Carvalho et al , ]. Furthermore, the use of an exponential current decay allows a direct comparison between results here and those previously reported by Jerauld [] and Howard et al [].…”
Section: Discussionsupporting
confidence: 58%
“…It is interesting that the average speed of the upward luminosity measured by Wang et al [] for triggered lightning dart‐stepped leaders is 6.7 × 10 7 m/s and the luminosity speed for the lowest pulses is near 8 × 10 7 m/s, whereas the speed of the upward current we must assume to match the waveform is higher, 1.1 to 1.5 × 10 8 m/s. According to the theory of Liang et al [], with some experimental confirmation by Carvalho et al [], the upward speed of the current is expected to be greater than the corresponding speed of the luminosity. Perhaps we are providing additional evidence that this is the case.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Recently, Carvalho et al . [, , ] have described measurements of the luminosity of very small (3.5 m) segments of channel starting 3 m above the ground termination, and they find a mean 10–90% optical risetime of 0.4 ± 0.1 us, that is only a factor of 2 less than the 0.8 ± 0.1 μs risetime that we measured in 2012 for a 62 m vertical length of channel. (The current risetimes were comparable in both experiments.)…”
Section: Discussionmentioning
confidence: 58%
“…Zhou et al [] reported that M‐component and initial continuous current (ICC) pulses in triggered lightning having risetimes in the range of 10 µs to 100 µs for both current and luminosity at the ground exhibited a current‐to‐luminosity delay on the order of the current and luminosity risetimes. Thus, from Carvalho et al [] and Zhou et al [], it would appear that the observed delay between current and luminosity at the ground increases with both increasing current risetime and increasing luminosity risetime.…”
Section: Introductionmentioning
confidence: 99%